The Religious Feminist Subject as Material-Discursive Circuit: A Christian Woman Reads and Re-reads Eve - Hovland, Ingie (Religion & gender, 2024)
This article describes three different readings of the creation story of Eve and Adam, occurring over the life span of Henny Dons, a Protestant Christian and first-wave feminist in early-twentieth-century Norway. I discuss her changing understandings of this creation account over the course of her life. More broadly I explore her approach to biblical reading (as receiving, arranging, and iterating) and how this shaped her as a religious feminist subject. I argue that what is going on in her iterated re-readings is not fully captured by the frame of self-cultivation. Rather, this religious feminist subject shows us a series of woman-word operations that receive and arrange a variety of material and discursive entities together in a circuit of “being created woman.”